PERAN DINAS SOSIAL DAN PEMAKAMAN DALAM PELAKSANAAN KEBIJAKAN PERLINDUNGAN ANAK DI KOTA PEKANBARU TAHUN 2012 - Ketler s, Sintong; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Child protection stipulated in Law No. 23 of 2002 . Children . because theyhave to be considered by the State , parents / families , as well as by localgovernments , namely the city of Pekanbaru . Child protection is an issue that must beconsidered . This is not only a national problem but the state has legal problems of allcountries in the world or global issues . It is the most under the spotlight in Pekanbarustill found many children affected by violence , psychological violence , physicalviolence , economic neglect , exploitation , trafficking , sexual abuse . One area thatwas highlighted in terms of the protection of children in the city of Pekanbaru is theSorcerer . Of the 12 districts in the city of Pekanbaru , Pekanbaru In this town a lotbecause of the violence in the city center terhadapdi pekanbaru city 's or Riauprovince where access to child abuse tend to be issues that do other rogue elements ofboth families / parents and the environment and people the people closest to the child.The purpose of this study was to determine the role of Social Service in theimplementation of child protection policies in Pekanbaru city in 2012 conducted bythe Women's Empowerment and Child Protection (P2TP2A), and the factors thatinfluence the role of Social Service in the implementation of child protection policiesin the city of Pekanbaru , 2012.Types and methods of research used is descriptive research, which is definedas the problem-solving process were investigated by exposing or describe the state ofthe subject and the object of research at the present time based on the facts as theyappear or. In collecting the data the authors conducted in-depth interviews andlooking for a variety of documents and official records.The results showed that there are several factors that affect the role of SocialService in the implementation of child protection policies in Pekanbaru city in 2012which is a factor of Communication, Resources, Disposition and bureaucracy thatdirectly affect the government's role in implementing the enforcement area.Communications made in the implementation of the government's role in theimplementation of child protection policies Social Agency in Pekanbaru in 2012under the protection of the child is running as it should.Keywords: Roles, Publik Orderliness, Implementation.